Asymmetric Homogeneous Hydrogenation of 2-Pyridones - Wysocki, Jędrzej; Schlepphorst, Christoph; Glorius, Frank (Synlett, 2015)
An asymmetric homogeneous hydrogenation of 2(1H)-pyridones has been developed, using a ruthenium complex bearing two chiral N-heterocyclic carbene (NHC) ligands. To the best of our knowledge, the presented reaction is the first example of a homogeneous asymmetric conversion of 2-pyridones into the corresponding enantioenriched 2-piperidones.
Keywords: asymmetric catalysis; hydrogenation; NHC; piperidone; pyridone